KERJASAMA KELOMPOK PRIMER SISWA DALAM PEMBELAJARAN DARING DI MTS AL-FATWA KUBU RAYA - Erna Rosita Dewi; Rustiyarso Rustiyarso; Supriadi Supriadi (Universitas Tanjungpura, 2022)
The title of this research is Primary Student Group Cooperation in Online Learning at MTs Al-Fatwa Kubu Raya. The purpose of this study was determine and describe the spontaneous cooperation and direct cooperation of primary groups of students in online learning at MTs Al-Fatwa Kubu Raya. This research uses descriptive method with qualitative research form. The data source of this research is students who have a primary group and homeroom teachers. Data collection tools in this study used observation guides, interview guides and documentation studies. The results showed that (1) the spontaneous cooperation of the primary group of students was evidenced by (a) remind primary group members to do assignments on time, (b) explain the material not yet understood by the primary group members as well, (c) reprimand members of the primary group who have not submitted their assignments, (2) direct cooperation of the student's primary group is evidenced by (a) perform tasks based on orders and (b) submit assignments on time